2017
DOI: 10.1371/journal.pone.0182752
|View full text |Cite
|
Sign up to set email alerts
|

A novel organotypic 3D sweat gland model with physiological functionality

Abstract: Dysregulated human eccrine sweat glands can negatively impact the quality-of-life of people suffering from disorders like hyperhidrosis. Inability of sweating can even result in serious health effects in humans affected by anhidrosis. The underlying mechanisms must be elucidated and a reliable in vitro test system for drug screening must be developed. Here we describe a novel organotypic three-dimensional (3D) sweat gland model made of primary human eccrine sweat gland cells. Initial experiments revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…In general, when using the hanging drop assay, factors that promote the formation of spheroids can be considered positive regulators of the developmental process. 53 , 54 Thus, HMWHA could be considered to be a positive cue for development of the MG. Interestingly, phalloidin staining revealed that in the center of the spheroids, the MG epithelial cells started to form acini ( Fig. 14 E).…”
Section: Resultsmentioning
confidence: 99%
“…In general, when using the hanging drop assay, factors that promote the formation of spheroids can be considered positive regulators of the developmental process. 53 , 54 Thus, HMWHA could be considered to be a positive cue for development of the MG. Interestingly, phalloidin staining revealed that in the center of the spheroids, the MG epithelial cells started to form acini ( Fig. 14 E).…”
Section: Resultsmentioning
confidence: 99%
“…Isolation of human EGs ex vivo that maintain their morphological integrity and function can also be an invaluable source for the cosmetic industry interested in studying the sweat response to pharmacological products in healthy as well as in pathologic disorders (eg anhidrosis, hypo‐ and hyperhidrosis). As a further fascinating challenge, the possibility exists of investigating the clinical outcome after transplanting exclusively EGs in special clinical situations, for example to extensive deep‐burn survivors whose scarring skin covered with skin grafts is devoid of sweat glands and suffers from heat intolerance …”
Section: Resultsmentioning
confidence: 99%
“…Cholinergic stimulation leads to intracellular Ca 2+ ‐uptake of secretory cells, followed by the opening of K + and Cl − channels, thus activating the NKCC1 cotransporter . An in vitro study by Klaka et al., using a calcium flux assay, showed that cholinergic stimulation with acetylcholine or pilocarpine gives rise to calcium influx in a 3D hanging drop culture model of eccrine sweat glands . Another study using confocal laser scanning microscopy showed that when two‐dimensional (2D) cultured sweat gland cells were stimulated by acetylcholine, an increase in intracellular calcium concentration occurs, similar to cells in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…[1,3,20] An in vitro study by Klaka et al, using a calcium flux assay, showed that cholinergic stimulation with acetylcholine or pilocarpine gives rise to calcium influx in a 3D hanging drop culture model of eccrine sweat glands. [21] Another study using confocal laser scanning microscopy showed that when two-dimensional (2D) cultured sweat gland cells were stimulated by acetylcholine, an increase in intracellular calcium concentration occurs, similar to cells in vivo. [22] However, there are no effective methods to detect fluid secretion of regenerated or reconstructed eccrine sweat glands.…”
Section: Discussionmentioning
confidence: 99%